Kendala Pengajaran Bahasa Indonesia dalam Masa Transisi Kurikulum Merdeka di SMP N 2 Mojogedang - Nila Prihartanti; Budhi Setiawan (Jurnal Inovasi Penelitian Ilmu Pendidikan Indonesia, 2024)
The learning process of Indonesian language subjects in the independent curriculum has several differences with the 2013 curriculum. The transition from the 2013 curriculum to the independent curriculum certainly has a long process and is carried out in stages. Just like the use of the independent curriculum at SMP N 2 Mojogedang which was carried out in stages as well. This article aims to review the learning activities and implementation of the independent curriculum in Indonesian language subjects at SMP N 2 Mojogedang during the transition period of implementing the independent curriculum. The writing of this article is based on a qualitative method with a case study approach and data collection techniques in the form of field research. Data collection was carried out by interviewing one of the Indonesian language subject teachers which was studied qualitatively and then analyzed by collecting data, processing data, and providing conclusions. From the results of the study, it can be seen that in the process of teaching and learning in Indonesian language subjects at SMP N 2 Mojogedang during the independent curriculum transition there are still many obstacles